Tuning polymorphism in 2, 3-thienoimide capped oligothiophene based field-effect transistors by implementing vacuum and solution deposition methods. Issue 21 (18th April 2018) - Benvenuti, Emilia; Gentili, Denis; Chiarella, Fabio; Portone, Alberto; Barra, Mario; Cecchini, Marco; Cappuccino, Chiara; Zambianchi, Massimo; Lopez, Sergio G.; Salzillo, Tommaso; Venuti, Elisabetta; Cassinese, Antonio; et al.
Abstract : The impact of the processing method in controlling the polymorphism and field-effect charge mobility of 2, 3-thienoimide-based oligothiophenes semiconductors was investigated. Abstract : We report on the investigation of the influence of the molecular packing and film morphology on the field-effect charge mobility in 2, 3-thienoimide-based oligothiophenes semiconductors (C n -NT4N). Organic field-effect transistors are realized by implementing both vacuum and solution methods in order to control the solid-state phase of the active layer. Thermal sublimation in a high vacuum chamber and supersonic molecular beam deposition were used as vacuum-based fabrication approaches for preparing thin films, while lithographically controlled wetting was used, as a solution-deposition technique, for the fabrication of the microstructured films. Thermal sublimation leads to thin films with a phase packing showing ambipolar behaviour, while supersonic molecular beam deposition enables, by varying the deposition rate, the formation of two different crystal phases, showing ambipolar and unipolar field-effect behaviours. On the other hand, lithographically controlled wetting enables the formation of C n -NT4N microstructured active layers and their implementation in field-effect transistors.